Field evaluation of cowpea cultivars (Vigna unguiculata L Walp.) for resistance to flower thrips (Megalurothrips sjostedti Trybom) (Thysanoptera: Thripidae) - Alabi, O.Y.; Odebiyi, J.A.; Jackai, L.E.N. (Informa UK Limited, 2003)
Ten cowpea cultivars were screened for resistance to flower bud thrips, Megalurothrips sjostedti, in replicated field trials. Resistance was evaluated by measuring differences in populations and visual damage on the cultivars. Statistical correlation was employed to assess the degree of association between damage indices and thrips population in the cultivars for each season. In the first season cultivars were conveniently grouped into three, using damage indices and thrips populations size. In the second season, due to the high thrips population, division into groups was not entirely achieveable; nevertheless the cultivars exhibited different resistance qualities. Sanzibanili, Moussa local, Sewe and IT90K-277-2 had consistently low damage indices and thrips population numbers, hence they performed better than the resistant control mu1509). TV x 3236 also performed well in the two seasons, but with slightly higher damage index and thrips numbers than the cultiiars aforementioned. IT91K-180 and Kpodjiguegue, while supporting a higher number of thrips than the other cultivars, also had larger number of pods, suggesting tolerance as their mechanism of resistance.